FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA PADA IBU BERSALIN - Ernida, Rosliana; Khresna Dewi, Vonny; Tunggal, Tri; Yuniarti, Yuniarti (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Preeclampsia is a serious pregnancy complication that occurs in about 3-8% of all pregnancies. The incidence of preeclampsia at Pambalah Batung Regional Hospital in 2024 was 10.65%. Several factors that increase the incidence of preeclampsia include maternal age, parity, history of hypertension, and history of preeclampsia. Objective: . To find out the factors associated with the incidence of preeclampsia in mothers giving birth at Pambalah Batung Regional Hospital in 2024. Methods: This study design was an observational analytical study with a case-control sample. The sampling technique used simple random sampling with a ratio of 258 cases: 258 controls. Data analysis used the Chi-Square test and dan Odss Ratio. Results: There were 258 mothers (50.0%) experienced preeclampsia. A total of 143 mothers (27.7%) were at risk (<20 years or >35 years). A total of 148 respondents (28.7%) had a parity at risk (1 child or more than 3 children). A total of 112 mothers (21.7%) had a history of chronic hypertension. A total of 127 mothers (24.6%) had a history of preeclampsia. Conclusion: There was a correlation between maternal age (P 0.002, OR 1,835), parity (P 0.011, OR 1,643), history of chronic hypertension (P 0.010, OR 1,741), and history of preeclampsia (P=0.011, OR 1,695) with the incidence of preeclampsia at Pambalah Batung Regional Hospital. Pambalah Batung Regional Public Hospital can develop strategies and evaluations to reduce the incidence of preeclampsia.